The Long-Term Impact of Bariatric Surgery on Development of Atrial Fibrillation and Cardiovascular Events in Obese Patients: An Historical Cohort Study - Yuan, Hongtao; Medina-Inojosa, Jose R.; Lopez-Jimenez, Francisco; Miranda, William R.; Collazo-Clavell, Maria L.; Sarr, Michael G.; Chamberlain, Alanna M.; Hodge, David O.; Bailey, Kent R.; Wang, Yutang; Chen, Yundai; Cha, Yong-Mei (Frontiers in Cardiovascular Medicine, 2021)
Objective: To determine whether early Roux-en-Y gastric bypass surgery (RYGB) reduces the risk of Major adverse cardiovascular events (MACE) in patients with obesity. Patients and Methods: We conducted a study of patients with class II and III obesity [body mass index (BMI) > 35 kg/m2] from Olmsted County, Minnesota, who underwent obesity clinic consultation between the years 1993–2012, and had either RYGB surgery within 1 year (RYGB-1Y group), or medically managed (No-RYGB group). The composite endpoint of MACE (all-cause mortality, stroke, heart failure admission and acute myocardial infarction) was the primary endpoint, with new-onset AF as the secondary endpoint. Results: Of the 1,009 study patients, 308 had RYGB-1Y and 701 were medically managed (No-RYGB). Overall, the age was 44.0 ± 12.4 (mean ± SD) years; BMI was 45.0 ± 6.8 kg/m2. The RYGB-1Y group had a lower rate of MACE (adjusted hazard ratio (HR), 0.62; 95% CI, 0.44–0.88; P = 0.008) and lower mortality (adjusted HR, 0.51; 95% CI, 0.26–0.96; P = 0.04) than the No-RYGB group. The RYGB-1Y surgery was not associated with lower AF occurrence (HR, 0.66; 95% CI, 0.40–1.10; P = 0.11). Conclusion: An early RYGB approach for BMI reduction was associated with lower rates of MACE.